Negative electrode and solid lithium secondary battery
Patent Information
- Application Number
- JP2025059475
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0018】 本発明によれば、固体リチウム二次電池の拘束圧を低くしても、充放電に伴う放電容量の低下を抑制することが可能な負極を提供することができる。
Smart Images

Figure 2026166505000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode used for solid lithium secondary batteries and a solid lithium secondary battery.
Background Art
[0002] In recent years, research and development on lithium metal secondary batteries that contribute to energy efficiency have been carried out to ensure that more people can access affordable, reliable, sustainable and advanced energy.
[0003] Patent Document 1 describes a negative electrode for a lithium metal battery that includes a lithium metal negative electrode, and a coating layer disposed on the lithium metal negative electrode and containing a carbon-based material and a polymer binder. Here, the carbon-based material is spherical graphene balls containing graphene and a silicon-based material. Further, the silicon-based material is SiOₓ (1<x<3).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of Invention
Problems to be Solved by the Invention
[0005] However, during charging of the lithium metal battery, lithium silicide (Li x Si y ) is generated, the coating layer expands, and the coating layer contracts during discharging of the lithium metal battery. For this reason, when the negative electrode for a lithium metal battery described in Patent Document 1 is applied to a solid-state battery and the restraining pressure is lowered, the discharge capacity may decrease with charge and discharge.
[0006] The present invention aims to provide a negative electrode that can suppress the decrease in discharge capacity associated with charging and discharging, even when the constraint pressure of a solid lithium secondary battery is low. [Means for solving the problem]
[0007] (1) A negative electrode used in a solid lithium secondary battery, comprising a negative electrode composite layer containing a negative electrode active material and a first solid electrolyte, wherein the negative electrode active material contains silicon and is covered by a coating layer, and the coating layer contains a second solid electrolyte and a polymer.
[0008] (2) The negative electrode according to (1), wherein the coating layer further comprises a conductive additive.
[0009] (3) The negative electrode according to (1), wherein the coating layer is made up of a first layer containing the second solid electrolyte and a second layer containing the polymer, which are sequentially laminated.
[0010] (4) The negative electrode according to (3), wherein the second layer further comprises a conductive additive.
[0011] (5) The negative electrode according to any one of (1) to (4), wherein the mass ratio of the negative electrode active material to the coating layer is 95:5 or more and 80:20 or less.
[0012] (6) The negative electrode according to (5), wherein the mass ratio of the negative electrode active material to the coating layer is 95:5 or more and 90:10 or less.
[0013] (7) The negative electrode according to any one of (1) to (4), wherein the volume ratio of the negative electrode active material to the coating layer is 73:27 or more and 69:31 or less.
[0014] (8) The negative electrode according to (7), wherein the volume ratio of the negative electrode active material to the coating layer is 73:27 or more and 71:29 or less.
[0015] (9) The negative electrode according to any one of (1) to (8), wherein the negative electrode active material is a silicon / carbon composite material.
[0016] (10) The negative electrode active material according to (9), wherein the negative electrode active material is a silicon / graphene composite material.
[0017] (11) A solid lithium secondary battery comprising the negative electrode according to any one of (1) to (10). [Effects of the Invention]
[0018] According to the present invention, it is possible to provide a negative electrode capable of suppressing a decrease in discharge capacity associated with charge and discharge even when the restraining pressure of the solid lithium secondary battery is lowered. [Brief Description of the Drawings]
[0019] [Figure 1] It is a cross-sectional view showing a part of the structure of a negative electrode mixture layer according to one embodiment of the present invention. [Figure 2] It is a cross-sectional view showing a part of the structure of a negative electrode mixture layer according to another embodiment of the present invention. [Figure 3] It is a cross-sectional view showing a part of the structure of a negative electrode mixture layer according to a comparative embodiment of the present invention. [Figure 4] It is a graph showing the discharge capacity at the first charge and discharge of the half cells of Example 1, Comparative Examples 1 and 2. [Figure 5] It is a graph showing the discharge capacity at the third charge and discharge of the half cells of Example 1, Comparative Examples 1 and 2. [Modes for Carrying Out the Invention]
[0020] Hereinafter, embodiments of the present invention will be described with reference to the drawings.
[0021] [Negative Electrode] The negative electrode of this embodiment is used in a solid lithium secondary battery and comprises a negative electrode composite layer containing a negative electrode active material 1 and a first solid electrolyte 2 (see Figure 1). The negative electrode active material 1 contains silicon and is covered by a coating layer 3. The coating layer 3 also contains a second solid electrolyte 31 and a polymer 32. Therefore, the negative electrode of this embodiment suppresses the decrease in discharge capacity associated with charging and discharging, even when the confinement pressure of the solid lithium secondary battery is low. This is presumed to be because even if the negative electrode active material 1 expands during charging and contracts during discharging, it is less likely to peel off at the interface between the coating layer 3 and the first solid electrolyte 2. Here, the coating layer 3 may further contain a conductive additive.
[0022] Alternatively, instead of the coating layer 3, the negative electrode active material 1 may be coated by a coating layer 4 in which a first layer 41 containing a second solid electrolyte and a second layer 42 containing a polymer are sequentially laminated (see Figure 2). Here, the second layer 41 may contain a conductive additive. Similarly, the second layer 42 may further contain a second solid electrolyte and a conductive additive. In this case, the second solid electrolyte contained in the second layer 42 may be the same as or different from the second solid electrolyte contained in the first layer 41.
[0023] On the other hand, if the negative electrode active material 1 is covered by a coating layer 5 that contains a second solid electrolyte and a conductive additive but does not contain a polymer, instead of the coating layer 3 (see Figure 3), the discharge capacity decreases with charging and discharging when the confinement pressure of the solid lithium secondary battery is lowered. This is presumed to be because when the negative electrode active material 1 expands during charging and contracts during discharging, it becomes more prone to delamination at the interface between the coating layer 5 and the first solid electrolyte 2.
[0024] The negative electrode active material 1 is not particularly limited as long as it contains silicon and is capable of intercalating and releasing lithium ions, but examples include silicon and silicon / carbon composite materials. Among these, silicon / graphene composite materials are preferred in terms of the discharge capacity of the solid lithium secondary battery.
[0025] The content of the negative electrode active material 1 in the negative electrode composite layer is not particularly limited, but for example, it is 50% by mass or more and 80% by mass or less.
[0026] The first solid electrolyte is not particularly limited as long as it is a material capable of conducting lithium ions, but examples include oxide-based electrolytes and sulfide-based electrolytes. Among these, sulfide-based electrolytes are preferred in terms of lithium ion conductivity.
[0027] The content of the first solid electrolyte in the negative electrode composite layer is not particularly limited, but is, for example, 20% by mass or more and 50% by mass or less.
[0028] The mass ratio of the negative electrode active material 1 to the coating layer 3 or coating layer 4 is preferably 95:5 or more and 80:20 or less, and more preferably 95:5 or more and 90:10 or less. When the mass ratio of the negative electrode active material 1 to the coating layer 3 or coating layer 4 is 95:5 or more, the decrease in discharge capacity associated with charging and discharging is suppressed even when the confinement pressure of the solid lithium secondary battery is low, and when it is 80:20 or less, the discharge capacity of the solid lithium secondary battery is increased.
[0029] The volume ratio of the negative electrode active material 1 to the coating layer 3 or coating layer 4 is preferably 73:27 or more and 69:31 or less, and more preferably 73:27 or more and 71:29 or less. When the volume ratio of the negative electrode active material 1 to the coating layer 3 or coating layer 4 is 73:27 or more, the decrease in discharge capacity associated with charging and discharging is suppressed even when the confinement pressure of the battery is low, and when it is 69:31 or less, the discharge capacity of the solid lithium secondary battery is increased.
[0030] The second solid electrolyte is not particularly limited as long as it is a material capable of conducting lithium ions, but examples include oxide-based electrolytes and sulfide-based electrolytes. Among these, sulfide-based electrolytes are preferred in terms of lithium ion conductivity.
[0031] The second solid electrolyte may be the same as or different from the first solid electrolyte.
[0032] The average particle size of the second solid electrolyte is preferably 50 nm or less, and more preferably 20 nm or less. When the average particle size of the second solid electrolyte is 50 nm or less, the discharge capacity of the solid lithium secondary battery increases, and the resistance of the negative electrode in this embodiment decreases. The average particle size of the second solid electrolyte is, for example, 5 nm or more.
[0033] If the average particle size of the second solid electrolyte exceeds 50 nm, the negative electrode active material 1 may be coated by the second solid electrolyte, potentially blocking the electron path necessary for the reaction. For this reason, as described later, it is preferable to use a coating layer 3 containing the second solid electrolyte, polymer, and conductive additive, or a second layer 42 containing the polymer and conductive additive.
[0034] The content of the second solid electrolyte in the coating layer 3 or coating layer 4 is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 30% by mass or less. When the content of the second solid electrolyte in the coating layer 3 or coating layer 4 is 20% by mass or more and 30% by mass or less, the decrease in discharge capacity associated with charging and discharging is suppressed even when the confinement pressure of the solid lithium secondary battery is lowered.
[0035] The polymer is not particularly limited as long as it has lithium ion conductivity, but examples include polyethylene oxide (PEO), polypropylene oxide (PPO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVdF), polyvinyl chloride, polydimethylsiloxane, and vinylidene fluoride-hexafluoropropylene copolymer. Among these, polyethylene oxide (PEO) is preferred in terms of lithium ion conductivity. Here, it is preferable that the polymer has high resistance to sulfide-based electrolytes, such as not causing side reactions.
[0036] The lithium-ion conductivity of the polymer is not particularly limited, but is, for example, between 0.01 mS / cm and 1 mS / cm.
[0037] The polymer content in coating layer 3 or coating layer 4 is preferably 1% by mass or more and 20% by mass or less, and more preferably 5% by mass or more and 10% by mass or less. When the polymer content in coating layer 3 or coating layer 4 is 5% by mass or more and 10% by mass or less, the decrease in discharge capacity associated with charging and discharging is suppressed even when the confinement pressure of the solid lithium secondary battery is lowered.
[0038] The coating layer 3 or the second layer 42 may further contain a conductive additive. This reduces the resistance of the negative electrode in this embodiment.
[0039] The conductive additive is not particularly limited as long as it has electronic conductivity, but an example is carbon black.
[0040] The content of the conductive additive in coating layer 3 or coating layer 4 is not particularly limited, but for example, it is 1% by mass or more and 5% by mass or less.
[0041] The method for coating the negative electrode active material 1 with the coating layer 3 is not particularly limited, but for example, a method of spray-drying a slurry containing the negative electrode active material 1, a second solid electrolyte 31, and a polymer 32 can be used. The method for coating the negative electrode active material 1 with the coating layer 4 is also not particularly limited, but for example, a method of forming a first layer 41 by spray-drying a slurry containing the negative electrode active material 1 and a second solid electrolyte, and then forming a second layer 42 by spray-drying the slurry containing the negative electrode active material 1 and polymer 32 on which the first layer 41 has been formed.
[0042] The negative electrode composite layer may further contain a binder, a conductive additive, etc. The binder is not particularly limited as long as it has binding properties, but an example is polyvinylidene fluoride. The conductive additive is not particularly limited as long as it has electronic conductivity, but an example is carbon black.
[0043] In this embodiment, the negative electrode has, for example, a negative electrode composite layer formed on a negative electrode current collector. The negative electrode current collector is not particularly limited, but examples include copper foil.
[0044] The method for forming the negative electrode composite layer is not particularly limited, but one example is to apply a coating solution containing the negative electrode active material 1 and the first solid electrolyte 2 onto the negative electrode current collector.
[0045] [Solid-state lithium secondary battery] The solid-state lithium secondary battery of this embodiment is equipped with the negative electrode of this embodiment. Examples of solid-state lithium secondary batteries include semi-solid-state lithium secondary batteries and all-solid-state lithium secondary batteries. All-solid-state lithium secondary batteries will be described below.
[0046] The all-solid-state lithium secondary battery comprises the negative electrode, positive electrode, and solid electrolyte layer of this embodiment. Here, the positive electrode has a positive electrode composite layer formed on a positive electrode current collector.
[0047] The positive electrode current collector is not particularly limited, but examples include aluminum foil.
[0048] The positive electrode composite layer contains a positive electrode active material and may further contain a solid electrolyte, a conductive additive, a binder, etc. The positive electrode active material is not particularly limited as long as it is capable of intercalating and releasing lithium ions, but examples include lithium nickel cobalt manganese composite oxide.
[0049] The solid electrolyte layer is, for example, a nonwoven fabric impregnated with a solid electrolyte. The solid electrolyte is not particularly limited as long as it is a material capable of conducting lithium ions, but examples include oxide-based electrolytes and sulfide-based electrolytes.
[0050] Although embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and the above embodiments may be modified as appropriate within the scope of the spirit of the present invention. [Examples]
[0051] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments. Note that "parts" refers to parts by mass.
[0052] [Example 1] A commercially available sulfide-based electrolyte with an average particle size of 700 nm was pulverized using a jet mill to obtain a sulfide-based electrolyte with an average particle size of 200 nm. The average particle size of the sulfide-based electrolyte was measured using a scanning electron microscope.
[0053] Lithium ion conductivity 1.4 × 10⁻⁶ -4 A slurry was obtained by dissolving or dispersing commercially available polyethylene oxide (mS / cm), a sulfide-based electrolyte with an average particle size of 200 nm, and commercially available acetylene black in isobutyronitrile in a mass ratio of 75:21:4. Next, the slurry was dropped onto a commercially available silicon / graphene composite material, which was to be used as the negative electrode active material, and then kneaded using a mortar to coat the negative electrode active material with a coating layer. At this time, the mass ratio and volume ratio of the negative electrode active material to the coating layer were 92:8 and 72:28, respectively.
[0054] Using a kneader, 70 parts of a negative electrode active material coated with a coating layer, 27 parts of a sulfide-based electrolyte with an average particle size of 200 nm, 1 part of acetylene black (commercially available) as a conductive additive, and 2 parts of polyvinylidene fluoride (commercially available) as a binder were dissolved or dispersed in butyl butyrate to obtain a coating solution for the negative electrode composite layer.
[0055] A negative electrode was obtained by applying a coating solution for the negative electrode composite layer to a copper foil, which serves as the negative electrode current collector, to form the negative electrode composite layer.
[0056] [Comparative Example 1] A negative electrode was obtained in the same manner as in Example 1, except that the negative electrode active material was not coated with a coating layer.
[0057] [Comparative Example 2] When manufacturing the coating solution for the negative electrode composite layer, instead of a sulfide-based electrolyte with an average particle size of 200 nm, a lithium ion conductivity of 1.4 × 10⁻¹⁰ is used. -4 A negative electrode was obtained in the same manner as in Comparative Example 1, except that a mixture of polyethylene oxide (PEO) at mS / cm and a sulfide-based electrolyte with an average particle size of 200 nm (mass ratio 78:22) was used.
[0058] [Half-cell manufacturing] After placing a sulfide solid electrolyte into a cylindrical ZrO2 tube, the tube was pressed between stainless steel jigs to obtain a solid electrolyte pellet. Next, the solid electrolyte pellet and the negative electrode were stacked, and then molding pressure was applied to form a solid electrolyte layer. Then, a lithium foil was stacked on the solid electrolyte layer on the side opposite the negative electrode, and then it was restrained with a restraining pressure of 3 MPa to obtain a half-cell.
[0059] [Half-cell discharge capacity] The half-cell was charged to the specified capacity with a constant current of 0.1C, left at the specified capacity voltage until the residual current was 0.01C or less, then discharged to 1.5V with a constant current of 0.1C, and left for 5 minutes. This process was repeated three times to charge and discharge the half-cell, and the discharge capacity was measured during the first and third charge-discharge cycles. Here, discharge capacity refers to the discharge capacity per gram of negative electrode.
[0060] Figure 4 shows the discharge capacity of the half-cells of Example 1 and Comparative Examples 1 and 2 during the first charge-discharge cycle. Figure 5 shows the discharge capacity of the half-cells of Example 1 and Comparative Examples 1 and 2 during the third charge-discharge cycle. Reference Example 1 is the case where the confinement pressure of the half-cell of Comparative Example 1 is set to 10 MPa.
[0061] Figures 4 and 5 show that the half-cell of Example 1 suppresses the decrease in discharge capacity during charging and discharging, even when the confinement pressure is low. In contrast, in the half-cells of Comparative Examples 1 and 2, the negative electrode active material is not covered by a coating layer, so when the confinement pressure is low, the discharge capacity decreases during charging and discharging. [Explanation of Symbols]
[0062] 1 Negative electrode active material 2 First solid electrolyte 3, 5 Covering layer 31 Second solid electrolyte 32 Polymers 41 1st layer 42 2nd layer
Claims
1. A negative electrode used in solid lithium secondary batteries, The negative electrode composite layer comprises a negative electrode active material and a first solid electrolyte, The aforementioned negative electrode active material contains silicon and is coated with a coating layer. The coating layer comprises a second solid electrolyte and a polymer, and is a negative electrode.
2. The negative electrode according to claim 1, wherein the coating layer further comprises a conductive additive.
3. The negative electrode according to claim 1, wherein the coating layer comprises a first layer containing the second solid electrolyte and a second layer containing the polymer, which are sequentially laminated.
4. The negative electrode according to claim 3, wherein the second layer further comprises a conductive additive.
5. The negative electrode according to claim 1, wherein the mass ratio of the negative electrode active material to the coating layer is 95:5 or more and 80:20 or less.
6. The negative electrode according to claim 5, wherein the mass ratio of the negative electrode active material to the coating layer is 95:5 or more and 90:10 or less.
7. The negative electrode according to claim 1, wherein the volume ratio of the negative electrode active material to the coating layer is 73:27 or more and 69:31 or less.
8. The negative electrode according to claim 7, wherein the volume ratio of the negative electrode active material to the coating layer is 73:27 or more and 71:29 or less.
9. The negative electrode according to any one of claims 1 to 8, wherein the negative electrode active material is a silicon / carbon composite material.
10. The negative electrode according to claim 9, wherein the negative electrode active material is a silicon / graphene composite material.
11. A solid lithium secondary battery comprising the negative electrode described in any one of claims 1 to 8.
Citation Information
Patent Citations
Anode for lithium metal battery and lithium metal battery including same
JP2021506090A